Realizing electronically reconfigurable intrinsic chirality: from no absorption to maximal absorption of any desirable spin - Khan Muhammad Ismail; Khan Tayyab Ali; Abdelbaky Moustafa; Wong Alex M. H. (Nanophotonics, 2025)
Circular dichroism – the spin-selective absorption of light – finds diverse applications in medicine, antennas and microwave devices. In this work, we propose and experimentally demonstrate an ultrathin electronically reconfigurable chiral metasurface which exploits the intrinsic symmetries of the meta-molecule to realize any spin absorption based on the handedness of the chirality chosen. We construct the left-chiral and right-chiral states by reconfiguring the meta-molecule into two enantiomeric states, which achieve strong circular dichroism exceeding 82 % at the design frequency of 9.5 GHz. The meta-molecule can be switched into a third (non-chiral) state which is isotropic and transparent. The achieved circular dichroism characteristics remain insensitive to incidence angles up to ±45°. The proposed reconfigurable chiral metasurface achieves left- and right- circular dichroism at the same frequency and with high efficiency, and is an attractive candidate for wide-ranging practical applications in imaging, wireless communication and medicine.